Live Streaming Architectures for Video Data - A Review - Ginimav, Ishwari; R., Prasad G.; Gowrishankar (Journal of ISMAC, 2020)
Video communication has become a crucial part of our everyday lives due to its ease of use and applicability. Also, the demand for video streaming services has grown exponentially due to the recent Covid19 situation. Over the years, researchers have formulated different algorithms and architectures for effective video streaming. Due to the presence of a large variety of algorithms, system designers are often unable to decide the most optimum video streaming architectures for effective system design. In this work, some of the most recent and effective streaming architectures and algorithms are discussed along with their performance metrics. This will assist readers in deciding the most optimum algorithms and architectures for their application. Along with the algorithmic comparisons, this text also recommends certain improvements in the reviewed algorithms for further improving their performance